Pengaruh Kepemimpinan Digital Kepala Sekolah dan Layanan Digital Sekolah terhadap Mutu Pendidikan di SMA Negeri 6 Lhokseumawe - Rahmy Zulmaulida; Nurasiah; Widia Sri Fitri Gayo; Edy Saputra (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study aims to determine the effect of the principal's digital leadership and school digital services on the quality of education at SMA Negeri 6 Lhokseumawe. This study uses a quantitative approach method. Data collection is done by using a questionnaire or questionnaire technique. The population is SMA N 6 Lhokseumawe, and the sample taken is 40 respondents. Data analysis techniques include analysis prerequisite tests, descriptive data analysis, and hypothesis testing. The results of the study show that: (1) the influence of the principal's digital leadership on the quality of education is significant, based on the level of significance (0.000 < 0.050) with a magnitude of 50.3%. Then the hypothesis is accepted (2) the effect of school digital services on theaquality of education is significant, based on the level of significance (0.000 < 0.050) with an effect of 41.9%. Then the hypothesis is accepted (3) the effect of the principal's digital leadership and school digital services on the quality of education is of simultaneous significance, based on the level of significance (0.000 < 0.050) with an effect of 64.8%, the hypothesis is accepted.